Relationship among neural response imaging threshold and behavioral comfort levels...15th International conferences on Cochlear Implants, Antwerp, Belgium, 27-30 June 2018 - Fanelli, K.; Pallares, N.; Diamante, V. (Journal of Hearing Science, 2018)
Programming Cochlear Implants (CI) takes a long time, more when behavioral responses are null or not reliable. Thus, different authors have developed studies of the NRI utility to find an effective MAP for auditory habilitation. Some authors have proposed that sequential behavioral programming in conjunction with electrophysiologcal test provide the best outcomes (Raghunandhan et al 2013). Others have written that Neural Response Imaging Thresholds (tNRI) can be clinically useful for programming CI (Caner et al 2007; Akin et al 2008; Van Den Abbeele et al 2012; Akin et al 2012). Objectives: The goals of this study are: 1) to describe tNRI changes from intraoperative to 6 months of use. 2) to evaluate the relationship among tNRI and behavioral comfort levels up to 6 months of CI use and 3) to analyzed NRI according to the site along the cochlea. Materials and methods:For this study we included 17 patients from Centro de Implantes cocleares Profesor Diamante (9 adults and 8 children). All with HR90K Advantage HiFocus MS cochlear implant. The single NRI measurement was done in odd electrodes intraoperatively, at the first month and between 3 and 6 months of CI use. Behavioral comfort levels were collected at the tune up, after 3 and 6 months of use. Subjects were evaluated using To find an optimal MAP we must combine objective measures with behavioral responses. The single tNRI is useful as a guideline to predict M level when behavioral responses are null or not reliable. But as exist differences between patients behavioral responses are mandatory. the Soundwave 3.0 programming software. All data collected were analyzed with Graph Pad Prism 6. Conclusion : For the first fitting intraoperative tNRI is useful to follow the pattern of neural response. tNRI intraoperative and M levels have statistically significant differences. Abstracts • 57--386 160 © J